A STUDY ON WAYS OF EXPRESSING POLITENESS IN BAD NEWS BUSINESS LETTERS IN ENGLISH - DANG THI THU TRANG (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Nowadays, in international business environment, businessmen have to expand their relationships with foreign partners to make more benefit. Therefore, they can use many methods to communicate. Among them, business letters are one of effective ways to convey views and information. Beside letters informing good news, businessmen also write bad news letters in their day-to-day transactions. However, it is not easy to write this kind of letters without giving offence to the readers, so the study will do research into some common ways of expressing politeness in letters of complaint, refusal and collection. The study will be divided into five chapters. It will begin with the rationale, aims and objectives, as well as research questions in the first chapter. Then, the prior studies of other researchers will be presented. Theoretical background is based on not only Brown and Levinson‘s theory but also useful knowledge of other authors. Chapter three will give research methodology as well as samples of the letters and procedure of doing the study. The most important part is chapter four which consists of the results including common ways of showing politeness and the approaches of organizing this kind of letters. Finally, from the findings above, some implications to write an effective bad news letters will be given in chapter five.